Correction: Aphid infestations reduce monarch butterfly colonization, herbivory, and growth on ornamental milkweed. - Bernadette M Mach; William Long; Jaret C Daniels; Adam G Dale (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288407.].